2021
DOI: 10.1101/2021.04.14.439740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fish functional diversity as an indicator of resilience to industrial fishing in Patagonia Argentina

Abstract: The relationship between fish functional diversity and fishing levels at which its baselines shift is important to identify the consequences of fishing in ecosystem functioning. For the first time, we implemented a trait-based approach in the Argentine Patagonian sea to identify the vulnerability and spatiotemporal changes in functional diversity of fish assemblages bycatch by a trawling fleet targeting the Argentine red shrimp Pleoticus muelleri (Spence Bate, 1888) between 2003 and 2014. We coupled seven fis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…To date, investigations of temporal change in marine ecosystems have focused on single populations [49,50]. However, it is becoming clear that multi-species, assemblage-based analyses [51,52], which include information on functional and taxonomic diversity, and potentially also phylogenetic diversity, will be important in tracking biodiversity change in these systems, predicting their resilience in the face of anthropogenic pressures [53], and in shaping conservation decisions and designing fisheries policy [5456]. As our investigation has shown, different dimensions of biodiversity change are not necessarily correlated.…”
Section: Discussionmentioning
confidence: 99%
“…To date, investigations of temporal change in marine ecosystems have focused on single populations [49,50]. However, it is becoming clear that multi-species, assemblage-based analyses [51,52], which include information on functional and taxonomic diversity, and potentially also phylogenetic diversity, will be important in tracking biodiversity change in these systems, predicting their resilience in the face of anthropogenic pressures [53], and in shaping conservation decisions and designing fisheries policy [5456]. As our investigation has shown, different dimensions of biodiversity change are not necessarily correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond those environmental and biological characteristics acting locally to drive the observed discreteness of stocks of D. brevicaudatus , differential fishing pressures can reinforce these patterns. Indeed, this skate is both subject to by‐catch (Ruibal Núñez et al, 2018; Rincón‐Díaz et al, 2021) and targeted by a fishery directed at skates in the northern regions of the Argentine Sea (Colonello & Cortés, 2014), where it suffers the greatest fishing pressure (Sánchez et al, 2011). Conversely, skates from NP were mostly caught by research cruises in a restricted area, imposed to protect juvenile hake (Irusta et al, 2016), where the fishing pressure is lower.…”
Section: Discussionmentioning
confidence: 99%
“…The longnose skate, Dipturus brevicaudatus (Marini, 1933) is a common component of the by‐catch in several Argentine fisheries (Paesch & Oddone, 2008), regularly occurring in red shrimp and hake fisheries (Estalles et al, 2011; Bovcon et al, 2013; Ruibal Núñez et al, 2018; Rincón‐Díaz et al, 2021). Cedrola, González & Pettovello (2005) reported that D. brevicaudatus is the most frequent accidentally caught skate in the red shrimp fishery operating in the Gulf of San Jorge where it comprises up to 55.6% of by‐catch weight.…”
Section: Introductionmentioning
confidence: 99%